Bibliometric Analysis to Evaluate Quality of Science in the Context of One CGIAR - CGIAR Advisory Services Shared Secretariat (CGIAR Advisory Services, 2022)
Science-Metrix developed this technical note to provide recommendations on the use of bibliometrics in mixed-methods evaluations and monitoring of Quality of Science (QoS) in One CGIAR research. As such, this technical note combines bibliometric expertise with inputs from CGIAR stakeholders and lessons from the independent evaluative reviews of the CRPs.